CHAETOTAXY OF LAST INSTAR CATERPILLAR OF CHALCIOPE HYPPASIA (CRAM.) A BEAN DEFOLIATOR (NOCTUIDAE) - SINGH, G. P.; GOEL, S. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
The relative length of coronal stem and frons, position of AF2 P2 puncture Fa, ocellar and subocellar groups on the head capsule punctures on prothoracic-shield and setae of SD and L groups on the prothorax and SD, and SV groups of abdomen are enumerated and elaborated as characters of taxonomic significance in the chaetotaxy of C. hyppasia (Cram.).